Mixed Coded RF/FSO EH-based Communication System subject to Multiuser interference and Residual hardware impairments - Labghough, Souad; Ayoub, Fouad; Bouanani, Faissal El; Belkasmi, Mostafa; Qaraqe, Khalid A. (IEEE access, 2023)
This study investigated the end-to-end performance of a coded dual-hop RF/FSO wireless communication system that operates across both Nakagami- m fading and Málaga- M atmospheric turbulence channels and are supplied with an amplify-and-forward semi-blind energy harvesting fixed-gain relay. Interestingly, an average bit error probability is obtained in terms of the Fox's H -function by taking into consideration multiple interferers in the first hop and residual hardware impairments at the relay and destination receivers. Finally, the study explores how the performance of the system under concern is impacted by convolutional self-orthogonal codes. The obtained results showed the suitability of the coding/decoding technique for the energy harvesting aided coded dual-hop communication system, which calls for high performance and minimal computing complexity.